Patient Preference for Once-Weekly Dosing in Type 2 Diabetes Mellitus in Japan - Rohini Sen; Alan L. Shields; Koichiro Atsuda (Journal of Health Economics and Outcomes Research)
**Background:** Among several factors that impair adherence to available therapies in type 2 diabetes mellitus (T2DM) is the complexity of the dosing regimen. Moreover, the value of a once-weekly (QW) administration of oral medications for T2DM compared to once, twice, or thrice daily (QD, BID, TID) regimens is unclear. This study aims to identify subgroups and patient characteristics correlated with a preference for QW dosing compared to daily dosing using survey-based methods.